2016
DOI: 10.1177/2042098616679813
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions in therapeutic hypothermia after cardiac arrest

Abstract: Background: Therapeutic hypothermia (TH) improves survival and neurologic function in comatose survivors of cardiac arrest. Many medications used to support TH have altered pharmacokinetics and pharmacodynamics during this treatment. It is unknown if or at what frequency the medications used during TH cause adverse drug reactions (ADRs). Methods: A retrospective chart review was conducted for patients admitted to an intensive care unit (ICU) after cardiac arrest and treated with TH from January 2009 to June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Nonetheless, 3 independent and validated scoring systems were used to strengthen the assessments made in this analysis, which is a suggested method reported in safety and adverse effect analyses. 18,19,28 The use of 3 tools does not mitigate the possibility that they could erroneously agree on the evaluation of an ADR, but this more rigorous approach was applied to increase the robustness of these assessments. Assessment of other agents' causing or contributing to these adverse events was not conducted as the assessment tools account for the presence of other possible contributing factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, 3 independent and validated scoring systems were used to strengthen the assessments made in this analysis, which is a suggested method reported in safety and adverse effect analyses. 18,19,28 The use of 3 tools does not mitigate the possibility that they could erroneously agree on the evaluation of an ADR, but this more rigorous approach was applied to increase the robustness of these assessments. Assessment of other agents' causing or contributing to these adverse events was not conducted as the assessment tools account for the presence of other possible contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…The use of 3 ADR detection tools has been reported as a more rigorous approach to accurately detect ADRs and was applied in an attempt to overcome limitations of retrospective review. 18,19 Duration of mechanical ventilation (MV), duration of hospital and ICU LOS, and mortality were reported, as well as discharge disposition. All statistics reported were descriptive in nature.…”
Section: Methodsmentioning
confidence: 99%
“…19 Consequently, in the clinical management of ECPR patients, numerous countries have embraced the use of physical and chemical methods, such as surface cold compress technology, intravascular cooling technology, nasal cooling devices and pharmaceutical agents, to swiftly achieve the target core temperature drop within intensive care units. [20][21][22][23][24] Nevertheless, in recent years, the implementation of therapeutic hypothermia in cardiac arrest patients undergoing ECPR has sparked some controversy. Recent studies have indicated that there were no marked differences in survival rates and the likelihood of favourable neurological outcomes between normothermia and hypothermia groups.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Witcher, et al have recently conducted a retrospective chart review of 229 patients admitted to an intensive care unit after cardiac arrest and treated with TH [75]. There were 670 possible ADRs i.e., an average of 3 for each patient treated with TH-and 69 probable ADRs identified.…”
Section: Liver Function and Drug Metabolismmentioning
confidence: 99%